2019
DOI: 10.1177/0958305x19852475
|View full text |Cite
|
Sign up to set email alerts
|

Bioethanol production from Madhuca latifolia L. flowers by a newly isolated strain of Pichia kudriavzevii

Abstract: There is a growing interest worldwide to search new, cheap and non-food biomass source for ethanol production. Bioethanol is a liquid fuel produced from renewable biomass source. In the present study, ethanol production from flowers of Madhuca latifolia trees was investigated by yeast strain isolated from milk whey. The isolated yeast was screened for fermentation ability by carbohydrate fermentation test and subjected to fermentation using M. latifolia flowers as substrate. The isolated yeast strain was ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 42 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…The inoculated plates were incubated at 30°C for 48 h. Based on microscopic examination and the colony color; different purified single colonies were subcultured in a GYP agar slant and incubated at 30°C for 24 h. After incubation, the pure culture was maintained at 4 °C for further study. 39 Quantitative estimation for bioethanol production by isolated yeast cells was performed after growing the tested cells in GYP broth for 72 h and inoculated with 24 h preculture at 0.2% concentration. Bioethanol production in the fermentation medium was monitored daily, where 1 ml sample was taken and centrifuged for 10 min at 11,000 rpm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The inoculated plates were incubated at 30°C for 48 h. Based on microscopic examination and the colony color; different purified single colonies were subcultured in a GYP agar slant and incubated at 30°C for 24 h. After incubation, the pure culture was maintained at 4 °C for further study. 39 Quantitative estimation for bioethanol production by isolated yeast cells was performed after growing the tested cells in GYP broth for 72 h and inoculated with 24 h preculture at 0.2% concentration. Bioethanol production in the fermentation medium was monitored daily, where 1 ml sample was taken and centrifuged for 10 min at 11,000 rpm.…”
Section: Methodsmentioning
confidence: 99%
“…Generally, different yeasts from many sources can be used as a source of bioethanol, including S. cerevisiae, Lachancea fermentati, Pichia kudriavzevii, Shizosaccharomyces pombe, Candida tropicalis, Zygosaccharomyces rouxii, Saccharomycodes ludwigii, Hanseniaspora guilliermondii, and Wickerhamomyces anomalus isolated from coconut inflorescence sap in Thailand, 69 P. kudriavzevii and Candida tropicalis from pineapple and mango, respectively, 70 Kluyveromyces marxianus from biscuit factories, 40 and P. kudriavzevii from milk whey. 39 Fermentation Initial fermentation using acid-alkali-treated RS and SCB. P. occidentalis strain AS.2 was tested for bioethanol production from the enzymatic hydrolysate of acid-alkali-treated RS and SCB.…”
Section: Enzymatic Hydrolysis Of Raw and Pretreated Rs And Scbmentioning
confidence: 99%
“…Similarly, in another study carried out by Rezania et al [48] their report indicated that bioethanol production optimization was achieved at temperature of 32 °C and higher pH of 6.0 [48]. However, some authors reported optimized pH of 4.5 [49] and lower temperature of 25 °C [50]. The differences observed in the optimized data could be attributed to different fermenting microorganisms used.…”
Section: Fermentation and Optimization Conditions Of Hydrolyzed Biomass To Ethanolmentioning
confidence: 96%